Legal Protection for Defamation Suspects Who Spread Facts on Social Media Reviewed from the ITE Law - Asis Asis (Faculty of Law, Muhammadiyah University of Surabaya, 2024)
This research wants to discuss the problem of defamation that is suspected of spreading facts on social media. This research is intended to understand the interpretation of Article 27 of the ITE Law as well as the Joint Decree of the Minister of Communication and Information Technology, the Attorney General, and the Chief of the National Police of the Republic of Indonesia on Implementation Guidelines for Certain Articles in the ITE Law. The research approach used is the Gap and Socio-Legal Analysis Study, which is an approach to study the implementation of the law on criminal procedure law and its relation to social impacts on law enforcement in Indonesia. The results of the study show that law enforcement officials always use Article 27 of the ITE Law to ensnare defamers on social media and override the Joint Decree of the Minister of Communication and Information, the Attorney General, and the Chief of the National Police of the Republic of Indonesia, so that the judge's decision is considered contradictory to the existing provisions. Keywords: Criminal Code, Defamation, ITE Law, Law Enforcement Officials